Seasonal variations of species composition and abundance of zooplankton in Ehoma Lake, a floodplain lake in Nigeria - I. Okogwu, Okechukwu. (2010)
Ehoma Lake is among the important breeding sites of the major fishes in the Mid-Cross River, Nigeria. The juveniles of these fishes are solely dependent on zooplankton, which has not been studied previously. I studied monthly the lake's physico-chemical variables and zooplankton composition in three stations (littoral, sub-littoral and pelagic) from March 2005 to August 2006. Sixty-seven zooplankton species (42 rotifers, 19 cladocerans and 6 copepods) were identified. Daphnia obtusa Kurz, Keratella valga Ehrenberg, Keratella ticinensis Callerrio, Keratella hiemalis Carlin, Brachionus dimidiatus Bryce and Lecane candida Hauer and Murray are new records for Nigeria. The dominant zooplankters were Diaphanosoma excisum Kurz and Moina micrura Kurz. There was an inverse relationship between species richness and abundance. Richness was highest in the dry season while peak zooplankton abundance was recorded in the rainy season. Zooplankton abundance and species richness decreased progressively from the littoral to the pelagic station while the Shannon-Weaver diversity index varied from 0.68 to 1.28 without a clear seasonal trend. There is a succession pattern: rotifers that are dominant in the dry season are replaced by cladocerans in the rainy season. This succession was greatly influenced by seasonal flooding of the lake. As no previous information on the zooplankton of the lake is available, this study provides baseline data on the lake`s zooplankton.